Brand Awareness, Halal Label, Subjective Norm Towards Purchase Intention Through Attitude as an Intervening Variable - Rusdianto, Hutomo; Ummah, Fiiki Khoirul (Global Health Science Group, 2022)
The purpose of the study is to test brand awareness, halal labels, subjective norms on purchase intention and attitude able to mediate. The research design used exploratory descriptive research using primary data and skunder. The data source is taken directly from respondents in the form of respondents' answers on the questionnaires distributed. The population and sample of the study were 100 respondents of the Management Study Program. The results of the study explained that brand awareness, halal labels, subjective norms positively increase attitude and brand awareness, halal labels, subjective norms, have a positive and significant effect on purchase intention, and brand awareness variables, halal labels, subjective norms, have a positive and significant effect on purchase intention through attitude as an intervening variable.